Natural Ventilation for Energy Efficient Office Buildings: A Comparative Analysis on Three Buildings In Kuala Lumpur - Naamandadin, Nurul Akmam; Zainol, Norrazman Zaiha; Mohd Noor, Siti Nur Aishah; Sapian, Abdul Razak (International Journal of Integrated Engineering, 2019)
The aim of this study was to identify and analyse the criteria of natural ventilation in the selected office buildings. The analysis had been made based on the architectural and passive design component provided in MS 1525:2007 for the office building. This case study is important in helping to understand the relationship between natural ventilation, energy efficiency and cost effectiveness.